Partial Protection From Lupus-Like Disease by B-Cell Specific Type I Interferon Receptor Deficiency - Keller, Emma J.; Patel, Neeva B.; Patt, Madeline; Nguyen, Jane K.; Jørgensen, Trine N. (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disease that can present with many different permutations of symptom presentation. A large subset of SLE patients have been shown to present with elevated interferon stimulated gene (ISG) expression, and Type I IFNs (IFNαβ) have been shown to drive disease in murine models through global IFNα Receptor (IFNAR) knockouts. However, the disease contribution of distinct immune cell subsets in response to constitutively increased levels of IFNαβ is not fully understood. We utilized a B-cell specific IFNAR knockout (BΔIFNAR) on the B6.Nba2 spontaneous-lupus background to determine the contribution of IFNαβ stimulated B cells in disease. We found that IFNαβ signaling in B cells is driving increased splenomegaly, increased populations of activated B cells, and increased populations of germinal center (GC) B cells, memory B cells, and plasma blasts/cells, but did not affect the development of glomerulonephritis and immune-complex deposition. IFNAR expression by B cells also drove production of anti-chromatin IgG, and anti-dsDNA and -nRNP IgG and IgG2C auto-antibody levels, as well as increased Bcl2 expression, affecting GC B cell survival in B6.Nba2 mice.